The relationship between industry profit and interest rate in Singapore : an exploratory study. - Chia, Min Liang. (2013)
This study explores interest rate and profit relationships at the industry level, in Singapore. Three major schools of thought, namely, the Ricardian, Marxian, and Keynesian schools, served as a theoretical foundation in guiding the study.